Critical environmental factors for transportation cycling in children: a qualitative study using bike-along interviews. - Ariane Ghekiere (Public Library of Science (PLoS), 2014)
Background Environmental factors are found to influence transport-related physical activity, but have rarely been studied in relation with cycling for transport to various destinations in 10-12 yr old children. The current qualitative study used 'bike-along interviews' with children and parents to allow discussion of detailed environmental factors that may influence children's cycling for transport, while cycling in the participant's neighborhood. Methods Purposeful convenience sampling was used to recruit 35 children and one of their parents residing in (semi-) urban areas. Bike-along interviews were conducted to and from a randomly chosen destination (e.g. library) within a 15 minutes' cycle trip in the participant's neighborhood. Participants wore a GoPro camera to objectively assess environmental elements, which were subsequently discussed with participants. Content analysis and arising themes were derived using a grounded theory approach. Results The discussed environmental factors were categorized under traffic, urban design, cycling facilities, road design, facilities at destination, aesthetics, topography, weather, social control, stranger danger and familiar environment. Across these categories many environmental factors were (in)directly linked to road safety. This was illustrated by detailed discussions of the children's visibility, familiarity with specific traffic situations, and degree of separation, width and legibility of cycle facilities. Conclusion Road safety is of major concern in this 10-12 yr old study population. Bike-along interviews were able to identify new, detailed and context-specific physical environmental factors which could inform policy makers to promote children's cycling for transport. However, future studies should investigate whether hypothetical changes to such micro environmental features influence perceptions of safety and if this in turn could lead to changes in children's cycling for transport.